Actual approaches to physical rehabilitation of patients with ischemic heart disease and complicated pathology after myocardium surgical revascularization - Kolodenko, Olena (ScienceRise: Medical Science, 2017)
The aim of the research is to assess the effectiveness of restoration treatment using hydrokinesotherapy in patients with ischemic heart disease (IHD) and concomitant pathology after surgical revascularization of the myocardium (SRM). Methods of the research. 280 patients with IHD and concomitant pathology after SRM were examined. 135 patients (group 1)received the standard treatment. 145 patients (group 2) received differentiated complexes of restoration treatment depending on the concomitant pathology adding hydrokinesotherapy. The groups were divided in subgroups depending on the concomitant pathology: А – concomitant arterial hypertension, B – diabetes mellitus, C – osteoarthritis. We realized the dynamic clinical observation of the objective and subjective patients’ states, instrumental and functional methods of examination (ECG, EchoCS, Holter monitoring of ECG, measurement of arterial pressure, heart rate, veloergometry, six-minute test (SMT). Results. After the course of rehabilitation patients of all groups demonstrated the improvement, but the statistically reliable one was observed in group 2. According to the results of six-minute test of walking (SMT), the increase of the distance by 30,0, 19,6 and 30,0% was observed in subgroup 2А, 2B, 2C corresponding to (p ≤ 0,05). The reliable increase of tolerance to a physical load was observed in patients of 2 group, in subgroup А1- by 80,4, in subgroup 2B - by 62,0, and in subgroup 3B - by 32,2% (p ≤ 0,05). Conclusions. Thus, the inclusion of hydrokinesotherapy in the complex differentiated programs of rehabilitation of patients with ICD and concomitant pathology after SRM is safe and effective, moreover, it favors the myocardium contractile ability and increase of tolerance to a physical load